The role of sphingosine-1-phosphate in the gut mucosal microenvironment and inflammatory bowel diseases - Zou, Fei; Wang, Su; Xu, Mengmeng; Wu, Zengrong; Deng, Feihong (Frontiers in Physiology, 2023)
Sphingosine-1-phosphate (S1P), a type of bioactive sphingolipid, can regulate various cellular functions of distinct cell types in the human body. S1P is generated intracellularly by the catalysis of sphingosine kinase 1/2 (SphK1/2). S1P is transferred to the extracellular environment via the S1P transporter, binds to cellular S1P receptors (S1PRs) and subsequently activates S1P-S1PR downstream signaling. Dysbiosis of the intestinal microbiota, immune dysregulation and damage to epithelial barriers are associated with inflammatory bowel disease (IBD). Generally, S1P mainly exerts a proinflammatory effect by binding to S1PR1 on lymphocytes to facilitate lymphocyte migration to inflamed tissues, and increased S1P was found in the intestinal mucosa of IBD patients. Notably, there is an interaction between the distribution of gut bacteria and SphK-S1P signaling in the intestinal epithelium. S1P-S1PR signaling can also regulate the functions of intestinal epithelial cells (IECs) in mucosa, including cell proliferation and apoptosis. Additionally, increased S1P in immune cells of the lamina propria aggravates the inflammatory response by increasing the production of proinflammatory cytokines. Several novel drugs targeted at S1PRs have recently been used for IBD treatment. This review provides an overview of the S1P-S1PR signaling pathway and, in particular, summarizes the various roles of S1P in the gut mucosal microenvironment to deeply explore the function of S1P-S1PR signaling during intestinal inflammation and, more importantly, to identify potential therapeutic targets for IBD in the SphK-S1P-S1PR axis.